The relationship between output growth and unemployment in the Philippines economy (1990-2014): an empirical analysis of variants of Okun’s Law / Marlon A. Mojica and Virgilio M. Tatlonghari. - Mojica, Marlon A.; Tatlonghari, Virgilio M. (Universiti Teknologi MARA Selangor, 2017)
This paper examines the empirical relationship between unemployment and real output in the Philippines utilizing quarterly data from the Labor Force Survey by the Philippine Statistics Authority for the period from 1990-2014. The study employed three variants of Okun’s Law – the “gap” approach, the “first difference” approach, and a dynamic approach. Findings show that the Okun’s coefficients based on the gap approach are consistent with the theoretical expectation of a negative relationship. In the ARDL model, labor force participation rate and trade openness were found to be significantly related to unemployment. The result of dummy variable test revealed the presence of structural break following the re-definition of unemployment in the Philippines in 2005. Recursive least squares and rolling regressions show evidence of parameter instability in several sub-periods.